Towards a Common Agricultural Data Space in the European Union: A Sustainable Development Perspective - Katarzyna Kosior (Wieś i Rolnictwo)
In February 2020 the European Commission announced a new strategy for data in which an innovative proposal to create a single European data space composed of many sectoral common data spaces, including the agriculture sector, was presented. It is expected that the common agricultural data space will provide support for delivering a smart, innovative and sustainable agri-food system from farm to fork. Based on the analysis of framework conditions for pooling and sharing agricultural data in the EU and the Commission’s initiatives in this area, this article aims to discuss how and to what extent the common data space in agriculture could contribute to environmental, economic and social sustainability in the EU. It was concluded that the achievement of sustainability goals with the help of the planned common data space remains challenging, particularly in the context of rapid, but uneven pace of digital transformation in the agri-food sector in the EU. Overcoming legal, technical and other barriers to data sharing in the EU will not remove the fundamental problems of limited representativeness of current agricultural data assets in the EU. The design of the common data space in agriculture as well as the rules for data access and use should therefore be carefully considered. Also, specific and datarelated intervention measures, e.g. under the CAP, would be needed both to decrease the problem of a fragmented farm data landscape and to respond to the growing needs to collect and share private farm data that are highly relevant to achieving broader social goals and sustainability.